Circulating tumor cells: advancing personalized therapy in small cell lung cancer patients - Prajwol Shrestha; Steven Kao; Veronica K. Cheung; Wendy A. Cooper; Nico vanZandwijk; John E. J. Rasko; Dannel Yeo (Molecular Oncology, 2025)
Small cell lung cancer (SCLC) is a highly aggressive cancer with a dismal 5‐year survival of < 7%, despite the addition of immunotherapy to first‐line chemotherapy. Specific tumor biomarkers, such as delta‐like ligand 3 (DLL3) and schlafen11 (SLFN11), may enable the selection of more efficacious, novel immunomodulating targeted treatments like bispecific T‐cell engaging monoclonal antibodies (tarlatamab) and chemotherapy with PARP inhibitors. However, obtaining a tissue biopsy sample can be challenging in SCLC. Circulating tumor cells (CTCs) have the potential to provide molecular insights into a patient's cancer through a “simple” blood test. CTCs have been studied for their prognostic ability in SCLC; however, their value in guiding treatment decisions is yet to be elucidated. This review explores novel and promising targeted therapies in SCLC, summarizes current knowledge of CTCs in SCLC, and discusses how CTCs can be utilized for precision medicine.